Editorial: Entrepreneurship Education - Krzysztof Wach (Jesuit University Ignatianum in Krakow, 2014)
Education plays a key role in shaping the attitudes, skills and culture, hence the actions of the European Union in recent years have aimed at promoting entrepreneurship as a separate course taught at all levels of education, from elementary up to the university level. In this respect, Europe lags behind the United States, where the elements of entrepreneurship education have been introduced into teaching programmes at the level of secondary education, and most universities offer compulsory or elective courses in entrepreneurship. Due to its importance for the whole of European society, the member state countries and their economies, entrepreneurship education should be included in the teaching curriculum not only in the fields of economics and/or business studies, but also in other fields of studies.